Isolation, Purification and Identification of Seven species of Algae in three drinking water plants supply springs in Sulaimani province and growth control of isolated algae by using some plant extracts - Bashar Tareq Ismael AL-Shandah; Riadh Abas Abd Al-Jabar; Trifa K. J. Farkha (Tikrit Journal of Pure Science)
In this study, three drinking water treatment plant supply springs were selected within different sites in Sulaimani province - Kurdistan region of Iraq. Samples were collected over period of eight months from May to the end of December 2015.